Rapid onset of perfused blood vessels after implantation of ECFCs and MPCs in collagen, PuraMatrix and fibrin provisional matrices1. (16th August 2013) - Allen, Patrick; Kang, Kyu‐Tae; Bischoff, Joyce
Abstract: We developed an in vivo vascularization model in which human endothelial colony‐forming cells (ECFCs) and human mesenchymal progenitor cells (MPCs) form blood vessel networks when co‐injected (ECFC + MPC) into nude mice in rat tail type I collagen, bovine fibrin or synthetic peptide PuraMatrix matrices. We used three approaches to determine the onset of functional vascularization when ECFC + MPC suspended in these matrices were implanted in vivo . The first was immunohistochemistry to detect vessels lined by human endothelial cells and filled with red blood cells. The second was in vivo vascular staining by tail vein injection of a mixture of Ulex europaeus agglutinin I (UEA‐I), a lectin specific for human endothelium, and Griffonia simplicifolia isolectin B4 (GS‐IB4 ), a lectin specific for rodent endothelium. The third approach employed contrast‐enhanced ultrasound to measure the perfusion volumes of implants in individual animals over time. Human endothelial‐lined tubular structures were detected in vivo on days 1 and 2 after implantation, with perfused human vessels detected on days 3 and 4. Contrast‐enhanced ultrasound revealed significant perfusion of ECFC + MPC/collagen implants on days 1–4, at up to 14% perfused vascular volume. ECFC + MPC implanted in fibrin and PuraMatrix matrices also supported perfusion at day 1, as assessed by ultrasound (at 12% and 23% perfused vascular volume, respectively). This model demonstrates that ECFC + MPC suspended in any of the three matrices initiated a rapid onset of vascularization. We propose that ECFC + MPC delivered in vivo provide a means to achieve rapid perfusion of tissue‐engineered organs or for in situ tissue repair. Copyright © 2013 John Wiley & Sons, Ltd.